Effect of Sesame Flour Type and Percentation on the Physicochemical and Organoleptic Properties of Combro Chips - Khoirina, Adhian Dini Khoirina; Susanto, Wahono Hadi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This research aimed to evaluate the application of the three types of sesame flour (white sesame flour, black sesame flour, and mixed sesame flour) and the addition of sesame flour at three different percentages (5%, 10% and 15%) on physicochemical and organoleptic characteristics of combro chips. Sesame flour has a potential functional seasoning alternative that could enhance nutritional value and consumer acceptability of traditional cassava-based snacks. This study uses a Completely Randomized Design (CRD) factorial with 2 factors. All quantitative data were analyzed using ANOVA (Analysis of Variance) with statistical software (?=5%). The study found that the type of sesame flour had no significant effect on the physical and chemical properties of combro chips, while increasing its percentage significantly influenced all attributes except moisture. Higher flour levels raised protein, fat, ash, and breaking force, indicating a firmer texture. Chips with 5% white sesame flour were most preferred for taste, texture, and color, whereas those with black and mixed sesame flour were less favored. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production